Monosubstituted, Anionic Imidazolyl Ligands from N−H NHC Precursors and Their Activity in Pd‐Catalyzed Cross‐Coupling Reactions. Issue 14 (21st June 2020) - Martinez, Erin E.; Jensen, Christopher A.; Larson, Alexandra J. S.; Kenney, Karissa C.; Clark, Kyle J.; Nazari, S. Hadi; Valdivia‐Berroeta, Gabriel A.; Smith, Stacey J.; Ess, Daniel H.; Michaelis, David J.
Abstract: We report that treatment of several 2‐diphenylphosphinoimidazoles with Pd(II) salts generates monosubstituted N−H NHC−Pd complexes via insertion into the C−P bond. Removal of the N−H proton in situ leads to anionic (X‐type) or imidazolyl‐Pd complexes that are highly stable and catalytically active, achieving up to 340, 000 turnovers at 1 ppm catalyst loading in Suzuki‐Miyaura reactions. DFT‐calculated Tolman electronic parameters for the sterically small ligands suggest that these ligands are significantly more donating than traditional NHCs, which provides a rationale for rapid cross‐coupling catalysis. Excellent reactivity is also demonstrated in Sonogashira reactions. Abstract :